Development of marine digital database system for navigational aid at coastal area - Mahmud, Mohd. Razali; Ghazali, Noorzalianee (2005)
This study is part of digital integrated coastal zone management system that is still under intensive research in several agencies in Malaysia. The foundation of this research is based on some parallel activities that occur in coastal area consisting of multiple agencies with multiple tasks but with one reason that is to make sure coastal activities are consistently smooth and flawless. A serious consideration has been given during the early stage of the system development considering it will involve lots of data, and lots of formats and scales which can lead to the wrong interpretation of the data. The expectation to this system is it can provide maximum assistant to coastal users for stringent navigation in port areas during berthing and departing of the ship. Furthermore, data that contains in this database will have an availability to assist the authority while making decision regarding things that occur in the coastal area.